COVID-19: A Possible Cause of Spontaneous Pneumoperitoneum - Ramos, Patrícia Varela (2023)
Introduction: Pneumoperitoneum is the presence of air within the peritoneal cavity and is mostly caused by organ rupture. Spontaneous pneumoperitoneum accounts 5% to 15% of the cases and occurs in the absence of organ damage. The pulmonary origin of pneumoperitoneum is unusual, and probably associated with mechanical ventilation and alveolar leak. In patients with coronavirus disease 2019 (COVID-19) there are some reports of air leak, like pneumothorax, pneumomediastinum, pneumoperitoneum, and subcutaneous emphysema. Case presentation: We present the case of a 70-year-old man with COVID-19 pneumonia admitted to the Intensive Care Unit (ICU). Since admission he was on Non-Invasive Ventilation (NIV), without improvement, needing Invasive Mechanical Ventilation (IMV) due to severe respiratory failure. Five days after IMV despite protective lung ventilation, massive spontaneous subcutaneous emphysema, pneumomediastinum and pneumoperitoneum were diagnosed. Besides initial conservative management 12 hours later, the patient developed abdominal compartment syndrome requiring percutaneous needle decompression. Conclusions: Pneumoperitoneum can be considered a rare complication of COVID-19 pneumonia and its management, resulting not only from the viral pulmonary but also from secondary causes. Conservative management should be usually enough. However, in the presence of abdominal compartment syndrome prompt recognition and treatment are crucial and eventually lifesaving.